A276 INVESTIGATING THE ROLE OF TTC7A THROUGH ITS INTERACTION WITH UBR5 TO MAINTAIN CELL SURVIVAL. (1st March 2018) - Dhingani, N; Guo, C; Warner, N; Murchie, R; Muise, A
Abstract: Background: Patients with mutations in Tetratricopeptide Repeat Domain 7A (TTC7A) results in a severe and untreatable form of inflammatory bowel disease with the majority dying before 2 years of age. Pathological features of these patients include intestinal apoptosis and disrupted apicobasal polarity. Since the molecular function of TTC7A is still poorly understood, we recently carried out a screen identifying potential TTC7A binding partners in an attempt to reveal its pathway of action. TTC7A is part of an evolutionarily conserved pathway and acts as a scaffolding protein recruiting phosphatidylinositol 4-kinase, PI4KIIIα, to the plasma membrane where it also binds to EFR3B. This conserved pathway helps PI4KIIIα phosphorylate phosphatidylinositol (PI) to PI-4-phosphate (PI4P) which has been implicated in cell survival and the maintenance of cell polarity. In addition, the E3 ubiquitin ligase, UBR5, was identified as a potential TTC7A binding protein and may play a role in stabilizing TTC7A protein levels. Furthermore, UBR5 is suggested to be a colorectal oncogene because it interacts with β-catenin to upregulate canonical Wnt signaling. UBR5 has also been implicated as a tumour suppressor gene and in regulating apoptosis. Aims: To understand the role of TTC7A and UBR5 in cell survival. We hypothesize that UBR5 is involved and required in the PI4KIIIα-TTC7A-EFR3B pathway to maintain cell survival. Methods: Vector constructs were created harbouring patient derived TTC7A mutations (E71K, Q526X, A832T) and expressed in HEK 293T cells. TTC7A immunoprecipitates (IP) were analyzed by tandem mass spectrometry identifying various binding proteins. To validate these potential TTC7A interacting proteins, co-IP was performed by co-transfecting cells with appropriate expression plasmids and then lysing the cells after 24hrs. Protein of interest was IP using the target antibody. Whole cell lysate and co-IP samples were subject to Western blot analysis. Results: Preliminary results show an interaction between the UBR5 and TTC7A along with the patient derived TTC7A variants. They also show the presence of PI4KIIIα in the UBR5/TTC7A complex. Furthermore, they suggest that β-catenin only interacts with UBR5 in the presence of TTC7A. Conclusions: The presence of PI4KIIIα in the UBR5/TTC7A complex implies that UBR5 is part of the conserved pathway to maintain cell survival through the downstream PI4P levels. Western blot analysis shows that UBR5 interacts most strongly with the TTC7A Q526X. A possible explanation is that the truncated TTC7A Q526X is ubiquitinated by UBR5 for proteasomal degradation, resulting in decreased PI4P levels. Also, the study suggests that TTC7A recruits β-catenin for ubiquitination by UBR5. Together, the research supports the notion that TTC7A is involved in multiple pathways with UBR5 to maintain cell survival or in causing colorectal cancer. Funding Agencies: None